Reflectance Measurement of N, P and K Content of Wollypod Vetch under Different N, P and K Fertilization - BASAYIGIT, LEVENT; ALBAYRAK, SEBAHATTIN (Asian Journal of Chemistry, 2010)
The objective of this study was to determine the relationships between nitrogen, phosphorus and potassium content of wollypod vetch (Vicia villosa ssp dasycarpa (Ten.) Cav) and spectral reflectance. Visible near-infrared reflectance spectroradiometer (VNIR) was used to predict the N, P and K content of wollypod vetch under different N (0, 20, 40, 60 and 80 kg ha), P (0, 30, 60, 90 and 120 kg ha) and K (0, 20, 40, 60 and 80 kg ha) fertilization. An experiment was conducted in the 2006 growing season in the Mediterranean region conditions of Turkey. Increasing N fertilization decreased spectral reflectance from 1.18 to 0.78 %. The highest spectral reflectance was obtained from control plot (1.19 %), while the least spectral reflectance was obtained from 60 kg ha P dose (0.82 %) in P fertilization. In K fertilization, the highest spectral reflectance was obtained from control plot (1.19 %), while the least spectral reflectance was obtained from 40 kg ha K dose (0.90 %). Woolypod vetch N, P and K content had high correlation with spectral reflectance. In N fertilization, the r2 of predicted and measured N, P and K were high (0.935, 0.797 and 0.884, respectively). In P fertilization, the r2 of predicted and measured N, P and K were (0.800, 0.886 and 0.928). In K fertilization, the r2 of predicted and measured N, P and K were (0.911, 0.851 and 0.859, respectively). Present results suggest that spectral reflectance in VNIR can be used for non-destructive prediction of forage N, P and K content in wollypod vetch under different fertilizations.